A Scientometric Analysis of the most Highly Cited Publications on Fracture Research from India: 1989–2022 - Vaishya, Raju; Gupta, Brij Mohan; Kappi, Mallikarjun; Vaish, Abhishek (Annals of the National Academy of Medical Sciences (India), 2023)
Background India bears a huge burden of accidents and fractures. This study aimed to study the bibliometric characteristics of India's fracture research output during last three decades. The most highly cited publications (HCPs; with 20 or more citations) on orthopaedic fracture research from India were analyzed on various parameters.Methodology The Scopus database was used to identify publications on fractures that originated from India, between 1989 to 2022. The top HCPs were retrieved. A bibliometric and network analysis was used to identify the key players, such as organizations, authors and journals, and important keywords besides identifying their collaborative interactions and visual co-occurrences of significant keywords using VOSviewer and Biblioshiny software.Results Of the total 1,048 Indian publications, 126 (10.02%) were HCPs (cited 4,695 times). External funding was received in 1.59%, and international collaboration in 15.08%. The most productive organizations were All India Institute of Medical Sciences (AIIMS), New Delhi, followed by Postgraduate Institute of Medical Education and Research (PGIMER), Chandigarh, and Pandit Bhagwat Dayal Sharma Post Graduate Institute of Medical Sciences (PGIMS), Rohtak. The most impactful organizations were Maulana Azad Medical College (MAMC), Delhi, followed by the Jawaharlal Institute of Postgraduate Medical Education & Research (JIPMER), Pondicherry, and Sancheti Institute of Orthopaedic Research & Rehabilitation, Pune. The most productive authors were R. Malhotra, M.S. Dhillon, and N.K. Magu, and the most impactful authors were U.K. Meena, A.P. Singh, and P. Sancheti. Delhi was the epic of research, followed by Karnataka, Tamil Nadu, and Chandigarh.Conclusion This study provides an insight into the research trends, the most influential contributions, and the performance of Indian organizations and authors. It gives some ideas about the past, present, and future hotspots in research.
Keywords: bone; fracture; orthopaedics; high-cited publications; India; scientometrics; bibliometrics; journals; institution; author